Exploring Vocabulary Competence through Wuthering Waves English Subtitles: The Perceptions of Indonesian EFL Learners - Hafiza Zia Rafi Izzati Zakaria; Shafa Shafa; Anis Komariah; Muhammad Tahir (GLENS: Global English Insights Journal, 2026)
The potential of authentic English input outside formal classrooms, such as that encountered in digital games, remains underexamined for Indonesian EFL learners at the college level. Authentic English input such as digital games comes with mandatory English subtitles, presenting an underexamined opportunity for incidental vocabulary learning. Therefore, this research uses a qualitative case study in order to examine how English department students perceived the role of intralingual English subtitles from the action role-playing game with the name Wuthering Waves in relation to their vocabulary competence. Seven respondents were chosen from three universities in Samarinda. The data from each respondent were analysed using thematic analysis, yielding several major themes as a result. It reveals that students view English subtitles within the game itself as a challenging but meaningful linguistic input. They actively employed digital tools to support their understanding of the game’s narrative context. Vocabulary familiarity was developed primarily through repeated exposure within the game context, including quests, character dialogues, and gameplay actions. It is concluded that non-localized games with English-only subtitles hold a significant pedagogical potential as supplementary resources for incidental learning outside formal classrooms situation.